HYGIENIC-SANITARY CONDITIONS OF DARK KITCHENS - Cavalini Sydrião, Erica Ismenia; Barbosa de Souza Almeida, Lorena; Bonfim de Melo, Milena Lidiani; Melo Batista , Bruna Aparecida (Cadernos ESP, 2023)
To assess the hygienic-sanitary conditions of dark kitchens in Fortaleza, Ceará, Brazil. This is an exploratory descriptive study. An instrument developed by ANVISA was used. The findings showed revealed heterogeneous profiles regarding the structure and complexity of services. The majority presented satisfactory hygiene conditions; however, all were classified as having unacceptable sanitary quality due to critical failures, with inadequate food temperature observed at some point in the production chain in 91% of the kitchens. In 45%, the food temperature remained adequate during transportation, and the type of dish influenced the results. The study provided support for the adoption of preventive measures and control of sanitary risks by kitchens and consumers. It is recommended to include other models of dark kitchens in future research.